THE ROLE OF RELATIONSHIP QUALITY AND LOYALTY PROGRAMS IN GROWING CUSTOMER LOYALTY - Wulantary, Cheritya; Fajar, Achmad; Abd Razak, Anis (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this study is to evaluate the role of relationship quality and loyalty program towards customer loyalty. The numbers of market players in the retails and consumer’s goods leads to a fierce competition. Customer have been given ample choices whether to buy their groceries from mini market, supermarkets or hypermarkets. There are so many choices and one of the ways to keep customer retain is through the loyalty program and possibly the relationship quality. A web-based survey was conducted for the purpose of data collections. The questionnaire was made online by with exactly same layout of the paper based concept. There are all together 25 items asked during the survey in which separated into 4 sections. Section A is related to respondent’s profile and section B is about the service quality followed by customer satisfaction and customer loyalty in section C and D. The questionnaires used 7 Likert scales to allow and attract more accurate answer in respondents. Respondents may choose their feedback from the rang number 1 to 7. Number 1 is strongly disagreeing and number 7 is strongly agree. A notice boards to announce about the survey was displayed with a barcode. The results show that both factors which are loyalty program and relationship quality do positively influence towards customer loyalty. It is about time where service providers to re-evaluate their marketing strategy and focused on giving additional benefits to the customers as compared to others. Service provider must start searching for their unique features that can be offered to customer. Customer loyalty is important as it provides a long term sustainability and survival in the markets.